Late Pliocene changes in the North Atlantic Current - Naafs, B. David A.; Stein, Ruediger; Hefter, Jens; Khélifi, Nabil; De Schepper, Stijn; Haug, Gerald H. (Earth and Planetary Science Letters, 2010)
ISSN:0012-821X ISSN:1385-013X